Influencing the Influencers: Diversification, Semantic Strategies, and Creativity Evaluations - Seong, Sorah; Godart, Frédéric C. (Academy of Management Journal, 2018)
Diversification can be risky, as it extends a firm’s identity across multiple categories. This study examines cultural and symbolic strategies used to mitigate such risks by managing the emergence of multiple identities. A key strategic choice is “naming;” the parent’s name may be included in the new subsidiary’s name (“semantic seeding”) or not (“semantic autonomy”). A stock of parent–subsidiary names serves as a lens through which gatekeepers evaluate the parent’s underlying creativity at the time of spanning categories. There is expected to be interfirm variance in creativity evaluations due to the differences in the number of autonomous or seeded names a parent sustains, the degree of visibility of different names, and the timing of introducing a new name. Using a panel dataset of global high-end fashion houses between 1998 and 2010, we found that each new autonomous subsidiary name enhanced the parent’s creativity appeal up to a certain point (an inverted U-shaped relationship). However, the predicted negative linear effect of seeded subsidiary names was not supported. Furthermore, gatekeepers’ ongoing memory of the focal firm was found to influence the parent’s perceived creativity. Our findings point to the possibility of using unfocused market presence for influencing the influencers.